False measurement of glycated hemoglobin in patients without hemoglobin A. Issue 1 (30th January 2019) - Suo, Minghuan; Wen, Dongmei; Wang, Weijia; Zhang, Decai; Xu, Shengnan; Wang, Xia; Hu, Ting
Abstract : Background : Hemoglobin (Hb) A1c, a biochemical marker widely used in monitoring diabetes mellitus, can be quantitatively measured by various examining systems. However, significant errors still exist. In the present study, we evaluated the HbA1c level in five patients with compound heterozygotes by five different examining systems and our goal is to identify the existence of erroneous HbA1c measurement. Methods: Blood samples collected from normal (no hemoglobin variants) and abnormal (compound heterozygotes) patients were analyzed by capillary electrophoresis technique and sequence analysis. The samples without HbA expression via above methods were further analyzed for HbA1c by ion exchange HPLC Variant II/ Variant II Turbo 2.0 (VII and VII-T 2.0), boronate affinity HPLC, capillary electrophoresis, and Tinaquant immunoassay. Results: HbA1c expression were unexpectedly detected in the compound heterozygous samples by using additional examining systems: The HPLC VII and VII-T 2.0 detected HbA1c expression in two of five samples and failed to detect the abnormal HbA2 expression; the CE system detected HbA1c expression in one of five samples with abnormal HbA2 expression; the Ultra2 and PPI system detected the HbA1c expression of all samples without abnormal HbA2 . Conclusions: Five human samples without HbA expression were additionally detected with HbA1c expression with or without abnormal HbA2 expression by five analysis systems and the different examining assay potentially affected the test results. These results demonstrated that the limitations of current examining systems for monitoring patients with hemoglobin disorders highlighting the further improvement in the method of clinical HbA examination.